If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6-5p+6=6-4p
We move all terms to the left:
6-5p+6-(6-4p)=0
We add all the numbers together, and all the variables
-5p-(-4p+6)+6+6=0
We add all the numbers together, and all the variables
-5p-(-4p+6)+12=0
We get rid of parentheses
-5p+4p-6+12=0
We add all the numbers together, and all the variables
-1p+6=0
We move all terms containing p to the left, all other terms to the right
-p=-6
p=-6/-1
p=+6
| T=35+7m | | 2=9+z/3 | | -(3b+15)=6(2b+5 | | (4x+72)=(8x+24) | | 2b-10=5b-24 | | 40-10g=-4g=16 | | 3x+74=81 | | j+3=42 | | (8x-11)+(15x)+(3x+9)=180 | | 5(f-4)=2(f+1) | | -56=7f | | -8k+6=-10k+1- | | j3=42 | | 2x(2)=444 | | 8(a-6)=-96 | | 18+7j=32 | | 6m=~9+5m | | 9x+8+3x-2=36 | | 10+1x=3x-4 | | 3-4x/2=7-(8x-4) | | 2.14=b-3 | | -22+30=-8p+4p | | 4(2x+3)=4x+36 | | 275=151-w | | y/6=20 | | 2(x-5+2)=5 | | 1/2y-y=6 | | Y=1/5(x-3)^2+4 | | 5(2x-3)-5x=5x-9 | | 10=x/4x +7 | | 9x–12=4x+13 | | -130=-7r-4 |